Genotype x environment interaction in water yam (Dioscorea alata) yield trials in five yamgrowing sites in Nigeria - Egesi, Chiedozie N.; Ogunyemi, S.; Asiedu, Robert (2005)
A randomised complete block experiment was conducted in the 1998 and 1999 cropping seasons in five major yam growing areas in the yam belt of Nigeria to evaluate the performance and yield stability of six genotypes of water yarn (Dioscorea alata L). Location, genotype and their interaction effects, significantly (P<0.001) affected fresh tuber yields. The best location for production, based on the general performance of genotypes, was the southern Guinea savanna, followed by the forest-savanna transition and then the humid forest ecology. Genotypes with good potential for multiple-tubering were identified. With respect to stability, two genotypes were identified to have given the most stable yields across all the five locations. The overall yields of these stable genotypes were above the mean yields for all the genotypes. The need for practical integration of yield and stability of performance is emphasized, and their benefits to breeders and farmers in selecting the best environmental treatments for good performance of crop varieties is highlighted.